Premodern Armenian Medicine, Tsaghik and Potential New Evidence for the Early History of Smallpox - Hambardzumyan, Naira; Postajyan, Vardanush; Zipser, Barbara (Studia Ceranea, 2025)
The paper presents new ethnomedical and philological evidence for a disease that is commonly identified as smallpox, predating the earliest known and convincing descriptions of the 10th century AD physician Rhazes. Our earliest source dates to the 7th century AD in Armenia. It refers to a disease called Tsaghik, which translates to flower, a name that is today in modern Armenian used to describe smallpox. We established a number of plant derived treatments for this disease. Moreover, we present preventative measures from Armenian folklore, some of which were still in use a few decades ago.